DEVELOPMENT OF STUDENT WORKSHEET BASED ON CONTEXTUAL TEACHING AND LEARNING - soffi widyanesti priwantoro; Citra Permata Sari; Syariful Fahmi; Widayati widayati (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
The students had difficulty in understanding comparative material in mathematics subject, especially its application in everyday life. In addition, there was no Contextual Teaching and Learning-Based Student Worksheet (LKPD) on comparative material. This research belonged to a development research that aimed to produce and determine the feasibility of Student Worksheet (LKPD) with CTL approach on comparative material. This research used Research and Development (R&D) method based on ADDIE model consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research were material experts, media experts and students of SMP Muhammadiyah 9 Yogyakarta. Data collection instruments of this research were interview and questionnaire. The validation results by material experts obtained an average score of 139 with good criteria, while the validation results by media experts obtained an average score of 172 with very goodÂ criteria. Based on the results of student responses, it was obtained an average score of 61.32 with good criteria. Therefore, it can be concluded that the Contextual Teaching and Learning-Based Student Worksheet on comparative material was feasible to use.